RISK ASSESSMENT OF THE PRESENCE OF SILENT MYOCARDIAL ISCHEMIA IN TYPE 2 DIABETIC PATIENTS - N. I. Volkova; J. A. Sorokina; A. V. Kharakhashyan; L. J. Shabanova (Медицинский вестник Юга России, 2013)
Purpose: testing in clinical practice a mathematical model of risk assessment of the presence of silent myocardial ischemia (SMI) in type 2 diabetic patients.Material and Methods: 55 type 2 diabetic patients have been studied; among them 26 (47,27%) men and 29 (52,73%) women, mean age – 57,79 ± 8,39 years, diabetes duration – 9,65 ± 6,41 years. Identified 11 parameters included in the model. Calculated and assessed the presence of factor SMI. To verify the diagnosis, all patients completed ECG monitoring with mandatory achievement of submaximal heart rate.Results: Higher risk of having SMI was detected in 14 (25.45%) patients, low risk - in 41 (74.54%). SMI was diagnosed in 10 (71.43%) patients at high risk. In patients at low risk SIM was not found. Thus, the sensitivity of the model was 100%, specificity - 91%, the positive predictive value - 71%, and the negative - 100%.Conclusions: This mathematical model assesses the risk of having a SMI in type 2 diabetic patients and can be used in actual practice to optimize early detection of this disease.